2021
DOI: 10.3390/cancers13153652
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibition in Advanced Non-Clear Cell Renal Cell Carcinoma: Leveraging Success from Clear Cell Histology into New Opportunities

Abstract: Renal cell carcinoma (RCC) is a histologically heterogeneous disease with multiple subtypes. Clear cell RCC (ccRCC) represents the most common histology and has thus been easiest to study in clinical trials. Non-clear cell RCC (nccRCC) represents about 25% of RCC tumors, with fewer treatment options available, compared to ccRCC, and with poorer outcomes. Non-clear cell RCC tumors are histologically diverse, with each subtype having distinct molecular and clinical characteristics. Our understanding of nccRCC is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Non-clear cell renal cell carcinoma (nccRCC) represents a heterogenous group of malignancies, making up 25% of all renal cell carcinoma cases [ 55 ]. Management of refractory metastatic nccRCC is a challenge given the variety in histology amongst these malignancies, with limited prospective data to guide treatment decisions in the refractory setting.…”
Section: Resultsmentioning
confidence: 99%
“…Non-clear cell renal cell carcinoma (nccRCC) represents a heterogenous group of malignancies, making up 25% of all renal cell carcinoma cases [ 55 ]. Management of refractory metastatic nccRCC is a challenge given the variety in histology amongst these malignancies, with limited prospective data to guide treatment decisions in the refractory setting.…”
Section: Resultsmentioning
confidence: 99%
“…However, its therapeutic efficacy in most cold tumors and PD-L1-negative solid tumors remains limited. Therefore, alternative therapeutic strategies are urgently required [ 141 ]. HSV-1 oncolytic virus, as an excellent gene vector, can not only effectively lyse tumor cells but also improve the TME by carrying various cytokines, which bodes well for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that PANK1 knockdown regulated mitochondrial bioenergetics and redox status, which is a critical mechanism underlying PANK1-mediated effects on ccRCC. Tumor-associated immune cells and immune checkpoint inhibition play important roles in the carcinogenesis and treatment of ccRCC (41). PANK1 has been shown to be correlated with the infiltration status of several types of immune cells.…”
Section: Discussionmentioning
confidence: 99%